Adaptation and of measure E5-vh in Colombian adolescents - Salamanca-Camargo, Yenny; Muela-Martínez, José Antonio; Espinosa-Fernández, Lourdes; Díaz-Castela, María del Mar (Pensando Psicología, 2025)
The purpose of this instrumental psychometric study was to carry out the cultural adaptation and validation of the Expressed Emotion Measure children’s version E5-vh in 503 adolescents between the ages of 12 and 17 years old, from the five regions of Colombia. The findings indicate that the content validation through expert judgment suggested adjustments in the wording of the items and revealed the need to eliminate item 8, while the reliability analysis showed the internal consistency and unidimensionality of the instrument, with an increase in the Cronbach’s alpha value to 0.7 when items 6 and 8 were eliminated. The construct validation through Exploratory Factor Analysis and Confirmatory Factor Analysis with independent samples indicated that the best model was the one composed of a single factor with 6 associated items. It is concluded that this is an evaluation measure with good psychometric properties that can be used for the evaluation and follow-up of Colombian adolescents’ perception of their parents’ levels of expressed emotion.